Efek Penambahan Ekstrak Jahe pada Bobot Komponen Karkas Ayam Broiler - Juliana Monika Nepa; Aditya Pamungkas (Lembaga Pengembangan Kinerja Dosen, 2025)
This study focuses on the weight of broiler chicken carcass components. This study aims to see the extent to which this treatment has an effect on the weight of broiler chicken carcass components. The study used 80 chickens, with feed given CP 11 and CP 12. This study with a Completely Randomized Design includes 4 treatments 5 replications. Treatments are P0 = P0 = Level 0% in 1 L of drinking water, P1 = Level 7.5% in 1 L of drinking water, P2 = Level 15% in 1 L of drinking water. P3 = Level 22.5% in 1 L of drinking water. The study used Analysis of Variance (ANOVA) to see significance (P <0.05) and continued with the Duncan test to see significant differences between treatments. The results of the study statistically provide a significant effect (P <0.05) on the breast weight variable, but not significant (P>0.05) on the thigh weight, wing weight, and back weight variables. It can be concluded that the addition of ginger extract has a positive effect on breast weight, thigh weight, wing weight, and back weight of broiler chickens.